Disparities in Pollution Capitalization Rates - Zivin, Joshua S. Graff,Singer, Gregor (National Bureau of Economic Research, 2022)
We examine how exogenous changes in exposure to air pollution over the past two decades have altered the disparities in home values between Black and White homeowners. We find that air quality capitalization rates are significantly lower for Black homeowners. In fact, they are so much lower that, despite secular reductions in the Black-White pollution exposure gap, disparities in housing values have increased during this period. An exploration of mechanisms suggests that roughly one-quarter of this difference is the result of direct discrimination while the remaining three-quarters can be attributed to systemic discrimination through differential access to complementary amenities
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Luftverschmutzung; Wohneigentum; Ethnische Diskriminierung; USA; Economics of Minorities; Races; Indigenous Peoples; and Immigrants; Non-labor Discrimination; Air Pollution; Water Pollution; Noise; Hazardous Waste; Solid Waste; Recycling; Housing Supply and Markets